2006
DOI: 10.3171/jns.2006.104.3.376
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of intracranial and spinal cavernous malformations: a study of prevalence and natural history

Abstract: As many as 40% of patients with a spinal CM may harbor a similar intracranial lesion, and approximately 40% of patients with coexisting spinal and intracranial CMs may have the nonfamilial (sporadic) form of the disease. Patients with symptomatic spinal CMs who are treated nonoperatively may have a small risk of clinically significant recurrent hemorrhage. The findings will aid in evaluation of surveillance images and in counseling of patients with spinal CMs, irrespective of family history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 32 publications
1
31
1
1
Order By: Relevance
“…In agreement with previously published pediatric series [13, 15, 23, 30], we observed that 83.3% of our 42 pediatric patients had supratentorial lesions, 11.9% infratentorial and 4.76% spinal CMs of the intra- and extradural compartments. We did not observe any cases of coexistent intracranial and spinal cavernomas, although this has been documented [35]. Among the intracranial sites, the frontal region is the most frequent location of cerebral CMs reported in pediatric series [10, 13, 20, 32, 33, 36], while basal ganglia CMs are less commonly reported in children than in adults [4, 13,37,38,39,40].…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…In agreement with previously published pediatric series [13, 15, 23, 30], we observed that 83.3% of our 42 pediatric patients had supratentorial lesions, 11.9% infratentorial and 4.76% spinal CMs of the intra- and extradural compartments. We did not observe any cases of coexistent intracranial and spinal cavernomas, although this has been documented [35]. Among the intracranial sites, the frontal region is the most frequent location of cerebral CMs reported in pediatric series [10, 13, 20, 32, 33, 36], while basal ganglia CMs are less commonly reported in children than in adults [4, 13,37,38,39,40].…”
Section: Resultsmentioning
confidence: 72%
“…Furthermore, the functional prognosis in children treated for spinal cord CMs seems better than in adults, although the neurological picture at clinical presentation commonly appears more severe in pediatric patients [10]. Asymptomatic intracranial lesions in children with symptomatic spinal CMs have been reported by Cohen-Gadol et al [35], confirming a higher risk for clinical evolution in patients with multiple CMs along the neuraxis [75]. Multiple spinal cord CMs in children are estimated to account for 16.6% of the published cases [10].…”
Section: Resultsmentioning
confidence: 99%
“…34,42 Acute neurological decline or recurrent episodes of acute decline with varying degrees of recovery are likely due to frank hemorrhage from the lesion. Our review of natural history studies revealed an overall 2.5% annual hemorrhage rate (range 0-4.5%), 3,10,25,36,38 similar to brainstem cavernomas. 5,8,15,20,27 Prior reviews of primarily case reports and small case series revealed retrospective annual hemorrhage rates of 1.4-1.6%.…”
Section: Natural History and Clinical Presentationmentioning
confidence: 99%
“…This phenomenon was carefully analyzed in 2 series. Cohen-Gadol et al 10 obtained cerebral MR images in 33 of 67 cases of spinal intramedullary CMs at their institution, finding 14 with associated cranial and spinal lesions. The mean age in this patient group was 40 years, 12 of the patients were Caucasian, and 8 of the patients had a family history of CMs.…”
Section: Natural History and Clinical Presentationmentioning
confidence: 99%
“…This fact needs further attention, and there are only limited data on the exact proportion of CCM patients with lesions of the spinal cord available in the literature. The probability that patients with CCM have a spinal cavernous malformation as well has been reported to be as high as 5%, and spinal cavernous malformations may have a higher rate of hemorrhage than CCMs [17,18,19]. …”
Section: Discussionmentioning
confidence: 99%